2018
DOI: 10.1016/j.cmet.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of the Reactive Metabolite Methylglyoxal Recapitulate Progression of Type 2 Diabetes

Abstract: The molecular causes of type 2 diabetes (T2D) are not well understood. Both type 1 diabetes (T1D) and T2D are characterized by impaired insulin signaling and hyperglycemia. From analogy to T1D, insulin resistance and hyperglycemia are thought to also play causal roles in T2D. Recent clinical studies, however, found that T2D patients treated to maintain glycemia below the diabetes definition threshold (HbA < 6.5%) still develop diabetic complications. This suggests additional insulin- and glucose-independent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 40 publications
3
119
0
Order By: Relevance
“…Interestingly, and while any impact on lifespan has not been studied, a very recent publication indicates that MGO exerts hormetic effects in S. cerevisiae, and possibly also in mammalian endothelial cells, notably at a concentration of 100 mM (Zemva et al, 2017), i.e., the exact concentration found to be effective in the current study in nematodes (Figure 3A). In addition and fully congruent with our results ( Figures 3A and 3B), recent findings in Drosophila indicate that MGO is capable of increasing lifespan (Moraru et al, 2018, in this issue of Cell Metabolism).…”
Section: Mgo Per Se Modulates Lifespan In a Hormetic Mannersupporting
confidence: 92%
“…Interestingly, and while any impact on lifespan has not been studied, a very recent publication indicates that MGO exerts hormetic effects in S. cerevisiae, and possibly also in mammalian endothelial cells, notably at a concentration of 100 mM (Zemva et al, 2017), i.e., the exact concentration found to be effective in the current study in nematodes (Figure 3A). In addition and fully congruent with our results ( Figures 3A and 3B), recent findings in Drosophila indicate that MGO is capable of increasing lifespan (Moraru et al, 2018, in this issue of Cell Metabolism).…”
Section: Mgo Per Se Modulates Lifespan In a Hormetic Mannersupporting
confidence: 92%
“…Furthermore, a knockout model of Glo1 in Drosophila resulted in elevated levels of MG, which recapitulated the metabolic disturbances of type 2 diabetes; i.e. insulin resistance and hyperinsulinemia, with eventual obesity and hyperglycemia (1). This raises the question of whether elevated MG formation might be involved in the pathogenesis of type 2 diabetes in humans.…”
Section: Discussionmentioning
confidence: 92%
“…Increased glycerogenesis implies triose generation from either glycolysis or fructolysis. The same trioses generate methylglyoxal (MG), the most toxic glycating agent known (1), which when increased recapitulates the phenotype of metabolic syndrome in animal models, even in the absence of hyperglycemia. We wondered whether hepatic fat and MG are parallel phenomena and/or are linked to metabolic flux dysfunction in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective reduction of MGO levels would reduce AGE formation and consequently inflammation. Indeed, the reduction of MGO is currently considered as a promising glucose independent strategy for retarding diabetic complications [19]. Like proteins, MGO can also bind peptides forming small AGE products.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a growing body of evidence has suggested that, in T2DM, oxidative stress and reduced activity of glyoxylase 1 are mainly responsible for accumulation of MGO which has many intraand extracellular targets with numerous deleterious effects including cell death, inflammation, impaired angiogenesis and macrovascular complications [18]. Recently, Moraru et al [19] demonstrated that elevated MGO levels contribute significantly to several aspects of T2DM pathogenesis including insulin resistance, obesity and hyperglycemia which suggests preventing the accumulation of this reactive metabolite is a beneficial therapeutic option against T2DM.…”
Section: Introductionmentioning
confidence: 99%